Peningkatan Motorik Kasar Anak Usia Dini Usia 4-5 Tahun Melalui Kegiatan Senam Irama - Desy Sinta Dewi; Iman Nurjaman; Evy Fitria (Pendidikan Guru PAUD Universitas PGRI Semarang, 2024)
Abstract This study looks at how rhythmic gymnastics practices may help young children (ages 4-5) develop their gross motor abilities. Evidence from previous studies shows that the formative years of a child's early years are crucial for the maturation of their gross motor skills, which include the use of their limbs and other major muscles. 17 students from TK Islam Al Bayan Tangerang participated as the subject research in this study, which followed a CAR methodology with two cycles of planning, doing, observing, and reflecting. A quantitative analysis was performed on data that had been gathered via observation, interviews, and documentation. According to the study's findings, 41% of the kids' gross motor abilities were in the